PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA PADA MATERI BANGUN RUANG MELALUI ANIMASI POWER POINT TERHADAP SISWA KELAS V SDN PARUNG PANJANG 06 - Wina Sae Mutia; Ima Mulyawati (Universitas PGRI Yogyakarta, 2021)
The rapid development of technology during the Covid 19 pandemic required educators to learn to use and utilize computer technology. This study aims to develop learning media for mathematics in building materials (cubes & blocks) through power point animations for fifth grade elementary school students, and to test the validity and practicality of learning media for geometric shapes through animation power points. The research method used, namely research and development (R&D) is researchÂ the ADDIE development model which consists of the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The test subjects were fifth grade students at SDN Parung Panjang 06. The instruments used were expert validation sheets, student and teacher response questionnaires. The result of this research is a video of learning mathematics on the material of building space (cube & block) class V. Development of learning video by using and utilizing animation on power point. The developed mathematics learning media has the criteria of